PEMBIASAAN MEMBACA HADIS DAN ARTINYA DALAM PENGEMBANGAN NILAI AGAMA ISLAM DI TK. ISLAM AL-KAUTSAR - Bai, Sri Tolu; Chiar, M; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Purpose of the research is to get information about ?Pembiasaan membaca hadis dan artinya dalam pengembangan nilai agama islam pada anak usia 5-6 tahun di TK Islam Al-Kautsar Pontianak?. Here, I used Descriptive Research Method with qualitative approach. The Media used by teacher is visual media that shaped illustrated story books, picture, and sometimes using video. The steps carried out by the teacher is with greetings, pray, and start question and answer. After that, the teachers prepare the book or materials for students reading hadith then students are invited to read the hadith together and that has been memorized at the point to become a leader in the group. Repeated alternately so that everything became familiar with the hadith that teach. The constraints of the students is some students won?t issue the voice so the teacher is difficult to know whether the students are already memorized or just don?t want to take their voice. The efforts made in habitual reading and the meaning of the hadith in the development of the value of Islam is the teacher invites other students to participate in the invited students who do not make a sound for reading hadith taught by the teacher.Keywords: Habituation, Hadis, The Development of Islamic Religious Values